(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Parkinson’s disease is a complex and progressive disorder characterized by various motor and non-motor symptoms. Movement disorders are the hallmark of PD and can severely compromise an individual’s ability to perform well-learned motor skills such as walking, writing, turning around, and transferring in and out of bed. Methodologies applied in patients are highly variable and many different approaches are used as per the stages of recovery. This limitation needs to be addressed by understanding and establishing a unique protocol that can be applied to these patients for better outcomes. Method: A 18 months study was conducted where patients diagnosed with Parkinson’s disease underwent physical therapy with validated module. The stage wise physical therapy module was prepared and validated with help of content validity, logical thinking and sensitivity analysis. Sample size was calculated and was 26 (By Thanchanok Pumprasart et al, With 95 % confidence and 80% power n= 26) . Functional independence measure, Modified Barthal index was assessed for functional independency and mobility. Result: Our results shower statistical significant improvement with stage wise rehabilitation protocol on various domains of mobility and cognitive functions. More ever it was also useful for maintaining the progress of disease. Conclusion: Stage wise physical therapy module was effective medium to reduce progression of disease and enhance mobility in Parkinson’s patients.